Sodium electric layered metal oxide positive electrode material with high rate and long cycle performance and preparation method of sodium electric layered metal oxide positive electrode material

By doping Li/Sr elements into the P2-type layered transition metal oxide positive electrode material, Na0.67Ni0.33Mn0.67-x-yLixSryO2 sodium-electric layered metal oxide positive electrode material was prepared, and its cycling performance and The problem of insufficient rate performance has achieved the preparation of high-efficiency and low-cost sodium ion battery positive electrode material.

CN119480986APending Publication Date: 2025-02-18CHANGZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411607572.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The cycling and rate performance of P2 layered transition metal oxide positive electrode material in sodium ion batteries is insufficient, and there are problems of poor structural stability and irreversible phase change.

Method used

By equimolarly changing Mn element to Li/Sr element, a sodium-electric layered metal oxide positive electrode material of Na0.67Ni0.33Mn0.67-x-yLixSryO2 was prepared, and the material was uniformized by high-temperature sintering process and ball milling mixing was used to improve the uniformity of the material. and structural stability.

Benefits of technology

It significantly improves the circulation and rate performance of the positive electrode material of sodium ion battery, reduces material costs, and is simple and environmentally friendly, suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005130025320000011
    Figure HDA0005130025320000011
  • Figure HDA0005130025320000012
    Figure HDA0005130025320000012
  • Figure HDA0005130025320000021
    Figure HDA0005130025320000021
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium-ion battery positive electrode materials, and particularly discloses a sodium-ion battery layered metal oxide positive electrode material with high rate and long cycle performance and a preparation method of the sodium-ion battery layered metal oxide positive electrode material. The irreversible dissolution of transition metal is inhibited; and the diffusion barrier of sodium ions in the sodium layer is reduced. The positive electrode material is in a flaky stacked irregular block shape and has a layered structure. According to the sodium electric layered metal oxide positive electrode material with high magnification and long cycle performance, the positive electrode material has better stability, the electrochemical performance is improved, meanwhile, the material cost is greatly reduced, and the preparation method is simple, low in cost and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and specifically relates to a sodium-ion battery layered metal oxide positive electrode material with high rate and long cycle performance and a preparation method thereof. Background Art

[0002] With the increasing depletion of non-renewable fossil energy, the energy crisis is becoming a focus of human society. In order to solve these energy and environmental problems, new energy sources such as solar energy, wind energy, and tidal energy are being vigorously developed. However, this type of energy has certain unfavorable conditions such as randomness and intermittency, which does not meet people's expectations. Therefore, it is of great practical significance to explore an efficient energy storage system. Since the development and research of lithium batteries, it has attracted social attention for its advantages such as light weight and high energy density. However, the content of lithium resources in the earth is not high, and the price of lithium-containing minerals is expensive and continues to rise. Therefore, my country needs a resource-rich and low-cost energy storage system that can partially replace lithium batteries. Therefore, sodium-ion batteries with lower costs but similar structures have gradually attracted the attention of scientific researchers.

[0003] For sodium-ion batteries, the cost of cathode materials accounts for more than 26% of the total cost of sodium-ion batteries. The most studied cathode materials are transition metal oxides, polyanionic compounds, Prussian blue analogs, and organic compounds. Layered transition metal oxides are widely considered to be the most promising materials for commercialization due to their advantages of convenient synthesis and low price, and they can share synthesis equipment and methods with commercial lithium-ion batteries. At present, the research on layered cathode materials is mainly focused on P2 and O3 types. P2 layered transition metal oxides have the advantages of environmental protection and simple preparation, and are currently the hot spot of sodium-ion battery cathode research. However, there are many problems with P2 layered oxide cathodes, such as low capacity, poor structural stability, and irreversible phase change. In view of these problems faced by P2 layered oxide cathodes, element doping strategies are widely used as the most effective and direct method to improve the electrochemical performance of sodium-ion batteries. Summary of the invention

[0004] The technical problem to be solved by the present invention is to improve the P2 type positive electrode material Na 0.67 Ni 0.33 Mn 0.67 The invention provides a double-element doped modified sodium ion battery layered metal oxide positive electrode material and a preparation method thereof.

[0005] To achieve the above object, the present invention adopts the following technical scheme: a sodium-electrode layered metal oxide positive electrode material with high rate and long cycle performance, the positive electrode material chemical formula is Na 0.67 Ni0.33 Mn 0.67-x-y Li x Sr y O2, wherein x+y≤0.67, x>0, y>0, the positive electrode material is an irregular block morphology of flake stacking and has a layered structure.

[0006] Furthermore, the positive electrode material has a chemical formula of Na 0.67 Ni 0.33 Mn 0.67-x-y Li x Sr y O2, where x+y≤0.67, 0 <x<0.1,0<y<0.1。

[0007] Furthermore, the positive electrode material has a chemical formula of Na 0.67 Ni 0.33 Mn 0.67-x-y Li x Sr y O2, where 0.005≤x≤0.015, 0.005≤y≤0.015.

[0008] Furthermore, the positive electrode material has a chemical formula of Na 0.67 Ni 0.33 Mn 0.65 Li 0.01 Sr 0.01 O2.

[0009] A method for preparing a sodium-electrode layered metal oxide positive electrode material with high rate and long cycle performance comprises the following steps:

[0010] S1. Mixing a sodium source, a nickel source, a manganese source, a lithium source and a strontium source according to a molar ratio in a chemical formula to obtain a mixture of raw materials.

[0011] S2. Drying the mixture.

[0012] S3. Sintering the dried raw material mixture at high temperature, and after cooling to room temperature, obtaining a sodium electrode layered metal oxide positive electrode material with high rate and long cycle performance.

[0013] Furthermore, in step S1, the sodium source is one or more combinations of sodium acetate, sodium carbonate, sodium nitrate, and sodium citrate; the manganese source is one or more combinations of manganese oxide, manganese trioxide, manganese hydroxide, manganese acetate, and manganese sulfate monohydrate; the nickel source is one or more combinations of nickel acetate tetrahydrate, nickel sulfate, nickel nitrate, and nickel trioxide; the lithium source is one or more combinations of lithium hydroxide, lithium carbonate, and lithium acetate; the strontium source is one or more combinations of strontium carbonate or strontium acetate.

[0014] Furthermore, the mixing method in step S1 is one of mortar grinding, ball milling mixing, and co-precipitation mixing.

[0015] Furthermore, the mixing method in step S1 is ball milling mixing, and the ball milling method is wet milling using ethanol, deionized water or a mixture of the two as a dispersant.

[0016] Furthermore, the ball milling speed is 200-400 r / min, and the time is 8-20 h.

[0017] Furthermore, the high temperature sintering in step S3 is: in an air atmosphere, first heating to 400-600°C at a heating rate of 2-6°C / min, sintering time 4-6h, then heating to 850-950°C at a heating rate of 2-6°C / min, sintering time is 10-25h.

[0018] Furthermore, during the high-temperature sintering process, in an air atmosphere, the temperature was increased to 500° C. at a rate of 2° C. / min, and the sintering time was 5 h; and then the temperature was increased to 900° C. at a rate of 2° C. / min, and the sintering time was 15 h.

[0019] The invention discloses an application of a sodium-ion battery layered metal oxide positive electrode material with high rate and long cycle performance, wherein the sodium-ion battery layered metal oxide positive electrode material is applied to a sodium-ion battery positive electrode material.

[0020] The beneficial effects of the present invention are:

[0021] A sodium-based layered metal oxide cathode material with high rate and long cycle performance 0.67 Ni 0.33 Mn 0.67-x- y Li x Sr y Based on the elemental composition of O2, by replacing the Mn element with Li / Sr elements in equal moles, and replacing Mn with inexpensive Li / Sr, the material cost can be greatly reduced.

[0022] The present invention mixes raw materials according to the elemental composition of the regulated positive electrode material, and synthesizes a sodium-electrolyte layered metal oxide positive electrode material with high rate and long cycle performance by a solid phase method. The preparation process is simple, low-cost, environmentally friendly, and suitable for large-scale industrial production.

[0023] The present invention uses Li / Sr to suppress Na 0.67 Ni 0.33 Mn 0.67 O2 undergoes an irreversible phase change, thereby stabilizing the structure, making the positive electrode material have better cycle performance and rate performance.

[0024] A sodium-electrolyte layered metal oxide cathode material with high rate and long cycle performance has excellent electrochemical properties, good cycle stability and good rate performance, which ultimately improves the electrochemical performance of the cathode material.

[0025] The preparation process of the present invention is simple, and only an appropriate amount of lithium and strontium elements are added to replace an equimolar amount of manganese, and no toxic or precious metals are introduced. The process is low in cost, environmentally friendly, and suitable for industrial production. In the preparation process of the present invention, the ball milling is wet milling using ethanol as a dispersant, and the wet milling using ethanol as a dispersant can fully wet the particle surface, which is beneficial to improving the ball milling efficiency. Secondly, the wet milling has no dust pollution problem, is beneficial to environmental protection, and improves the working environment of the factory area. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Preparation of Na for Example 1 0.67 Ni 0.33 Mn 0.65 Li 0.01 Sr 0.01 SEM image of O2;

[0027] Figure 2 Preparation of Na for Example 1 0.67 Ni 0.33 Mn 0.65 Li 0.01 Sr 0.01 Rate performance diagram of O2;

[0028] Figure 3 Preparation of Na for Example 2 0.67 Ni 0.33 Mn 0.65 Li 0.02 SEM image of O2;

[0029] Figure 4 Preparation of Na for Example 2 0.67 Ni 0.33 Mn 0.65 Li 0.02 Rate performance diagram of O2;

[0030] Figure 5 Preparation of Na for Example 3 0.67 Ni 0.33 Mn 0.65 Sr 0.02 SEM image of O2;

[0031] Figure 6 Preparation of Na for Example 3 0.67 Ni 0.33 Mn 0.65 Sr 0.02 Rate performance diagram of O2;

[0032] Figure 7 Preparation of Na for Example 4 0.67 Ni 0.33 Mn 0.67 SEM image of O2;

[0033] Figure 8 Preparation of Na for Example 4 0.67 Ni 0.33 Mn 0.67 Rate performance diagram of O2;

[0034] Fig. 9 Preparation of Na for Example 4 0.67 Ni 0.33 Mn 0.66 Li 0.005 Sr 0.005 SEM image of O2;

[0035] Fig.10 Preparation of Na for Example 5 0.67 Ni 0.33 Mn 0.66 Li 0.005 Sr 0.005 Rate performance diagram of O2;

[0036] Fig.11 Preparation of Na for Example 6 0.67 Ni 0.33 Mn 0.64 Li 0.015 Sr 0.015 O2SEM image;

[0037] Fig.12 Preparation of Na for Example 6 0.67 Ni 0.33 Mn 0.64 Li 0.015 Sr 0.015 Rate performance diagram of O2;

[0038] Fig.13 The graphs are the cycle performances of materials prepared under different embodiments. DETAILED DESCRIPTION

[0039] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0040] A method for preparing a sodium-electrode layered metal oxide positive electrode material with high rate and long cycle performance comprises the following steps:

[0041] S1. Sodium carbonate, nickel trioxide, manganese dioxide, strontium carbonate, and lithium carbonate are added to a ball mill in sequence according to the molar ratio in the chemical formula, and an appropriate amount of anhydrous ethanol is added to fully mix these raw materials by ball milling to obtain a raw material mixture;

[0042] S2, drying the raw material mixture;

[0043] S3. Sintering the dried raw material mixture at high temperature, and after cooling to room temperature, obtaining a sodium electrode layered metal oxide positive electrode material with high rate and long cycle performance.

[0044] Example 1

[0045] First, weigh 0.373g of anhydrous sodium carbonate (5% excess), 0.5651g of manganese dioxide, 0.2728g of nickel trioxide, 0.0037g of lithium carbonate, and 0.0147g of strontium carbonate into a ball mill, add 5ml of anhydrous ethanol for ball milling, the ball milling speed is 225r / min, and the ball milling time is 12h. Secondly, the mixed slurry obtained by ball milling is placed in a blast drying oven for drying, and the powder is ground to obtain a uniform powder. Finally, the powder is placed in a muffle furnace for air sintering; the sintering procedure is to increase the temperature to 500℃ at 2℃ / min and keep it warm for 6h; then increase the temperature to 900℃ at 2℃ / min and keep it warm for 15h, and then let it cool naturally to obtain the active material Na 0.67 Ni 0.33 Mn 0.65 Li 0.0 1Sr 0.01 O2.

[0046] The same process was used to synthesize Example 2Na 0.67 Ni 0.33 Mn 0.65 Li 0.02 O2, Example 3Na 0.67 Ni 0.33 Mn 0.65 Sr 0.02 O2, Example 4Na 0.67 Ni 0.33 Mn 0.67 O2, Example 5Na 0.67 Ni 0.33 Mn 0.66 Li 0.005 Sr 0.005 O2 and Example 6Na 0.67 Ni 0.33 Mn 0.64 Li 0.015 Sr 0.015 O2.

[0047] By the attached Figure 1 , 3, 5, and 7, it can be seen that the synthesized sodium-electrolyte layered metal oxide cathode material is a material in which irregular flakes are stacked into layers;

[0048] The layered oxide positive electrode materials prepared in Examples 1-6 were used to prepare sodium ion batteries and their performance was tested.

[0049] The specific steps for preparing a sodium-electrode layered metal oxide positive electrode material electrode with high rate and long cycle performance are as follows:

[0050] 160 mg of the layered oxide positive electrode material Na prepared in Example 1-6 0.67 Ni 0.33 Mn 0.65 Li 0.01 Sr 0.01 O2、Na 0.67 Ni 0.33 Mn 0.65 Li 0.02 O2、Na 0.67 Ni 0.33 Mn 0.65 Sr 0.02 O2、Na 0.67 Ni 0.33 Mn 0.67 O2、Na 0.67 Ni 0.33 Mn 0.66 Li 0.005 Sr 0.005 O2、Na 0.67 Ni 0.33 Mn 0.64 Li 0.015 Sr 0.015 O2 was put into a mortar with conductive agent superP and polyvinylidene fluoride PVDF powder in a mass ratio of 8:1:1 and fully ground for 20 minutes to obtain a mixture; then 360 mg of N-methylpyrrolidone was added to the mixture in a weight ratio of PVDF:NMP=1:18 and stirred to obtain a mixed slurry; then the slurry was coated on aluminum foil (the height of the scraper used was 100 microns), and then the aluminum foil was placed in a vacuum drying oven for drying (first at 80°C for 4 hours. Then at 120°C for 12 hours under vacuum). The dried electrode sheet was cut into a circular electrode sheet with a diameter of 12 mm using a pole sheet punch for standby use, and the battery was assembled for testing.

[0051] The assembled sodium ion battery was placed at about 30°C for 24 hours, and tested at different rates (the voltage range of charge and discharge was 2.0-4.2V). The capacity retention performance of the sodium ion battery in each embodiment is as follows: Figure 2 , 4 , 6, 8, 10 and 12.

[0052] After single doping modification with lithium or strontium, its initial capacity has decreased compared with that of undoped cells, but its stability has been improved, especially when switching between different rates, the capacity stability has been significantly improved. 0.67 Ni 0.33 Mn 0.65 Li 0.01 Sr 0.01 The initial capacity of the electrode prepared by O2 material also decayed to a certain extent, but its stability was better than that of the undoped or single element doped electrode, especially at high rate (20C), it still had a reversible specific capacity of 70mAh / g. The most significant feature of its advantages is its cycle performance.

[0053] The assembled sodium ion battery was left to stand at about 30°C for 24 hours, and then the performance of the sodium ion battery was tested at the same temperature with a charge and discharge rate of 1C (the charge and discharge voltage range was 2.0 to 4.2V). The cycle performance of the sodium ion battery is shown in the figure below: Fig.13 shown.

[0054] Depend on Fig.13 It can be seen that the cycling performance of each material at 1C rate is as follows Fig.10 As shown in Figure 2, during the 300-cycle cycle, the combined doping modified material has the highest reversible specific capacity and excellent stability. It is worth noting that after 300 cycles, the Na 0.67 Ni 0.33 Mn 0.65 Li 0.01 Sr 0.01 The capacity retention rate of the electrode made of O2 material is still above 90%, which has very excellent cycle performance, while the positive electrode material modified by lithium doping has a higher reversible specific capacity than it.

[0055] Therefore, lithium and strontium in the modified Na 0.67 Ni 0.33 Mn 0.67 O2 materials have a synergistic effect. Strontium doping can improve its stability performance, and lithium doping can change its capacity performance.

[0056] The present invention synthesizes a sodium-ion battery layered metal oxide positive electrode material with high rate and long cycle performance by solid phase method, and replaces the expensive and toxic Mn element with lithium and strontium elements, thereby reducing the preparation cost of the positive electrode material of the sodium ion battery. The lithium and strontium elements are doped in the transition metal layer and the sodium layer respectively, which has a positive joint modification effect on reducing the diffusion barrier of sodium ions and inhibiting the irreversible dissolution and migration of transition metals.

[0057] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. A sodium-electrode layered metal oxide positive electrode material with high rate and long cycle performance, characterized in that: The chemical formula of the positive electrode material is Na 0.67 Ni 0.33 Mn 0.67-x-y Li x Sr y O2, where x+y≤0.67, x>0, y>0.

2. According to claim 1, a sodium-electrode layered metal oxide positive electrode material with high rate and long cycle performance, characterized in that: The chemical formula of the positive electrode material is Na 0.67 Ni 0.33 Mn 0.67-x-y Li x Sr y O2, where x+y≤0.67, 0 <x<0.1,0<y<0.1。 3. The low-nickel layered oxide positive electrode material according to claim 2, characterized in that: The chemical formula of the positive electrode material is Na 0.67 Ni 0.33 Mn 0.67-x-y Li x Sr y O2, where 0.005≤x≤0.015, 0.005≤y≤0.

015.

4. A method for preparing a sodium-electrode layered metal oxide positive electrode material with high rate and long cycle performance according to any one of claims 1 to 3, characterized in that: The steps include: S1, mixing a sodium source, a nickel source, a manganese source, an iron source and a magnesium source according to a molar ratio in a chemical formula to obtain a mixture of raw materials; S2, drying the raw material mixture; S3. Sintering the dried raw material mixture at high temperature, and after cooling to room temperature, obtaining a sodium-electrode layered metal oxide positive electrode material with high rate and long cycle performance.

5. The method for preparing a sodium-electrode layered metal oxide positive electrode material with high rate and long cycle performance according to claim 4, characterized in that: In step S1, the sodium source is one or a combination of sodium acetate, sodium carbonate, sodium nitrate, and sodium citrate; the manganese source is one or a combination of manganese oxide, manganese trioxide, manganese hydroxide, manganese acetate, and manganese sulfate monohydrate; the nickel source is one or a combination of nickel acetate tetrahydrate, nickel sulfate, nickel nitrate, and nickel trioxide; the lithium source is one or a combination of lithium hydroxide, lithium carbonate, and lithium acetate; and the strontium source is strontium carbonate or strontium acetate.

6. The method for preparing a sodium-electrode layered metal oxide positive electrode material with high rate and long cycle performance according to claim 4, characterized in that: The mixing method in step S1 is one of mortar grinding, ball milling mixing, and co-precipitation mixing.

7. The method for preparing the low-nickel layered oxide positive electrode material according to claim 6, characterized in that: The mixing method in step S1 is ball milling mixing, and the ball milling method is wet milling using ethanol as a dispersant.

8. The method for preparing a sodium-electrode layered metal oxide positive electrode material with high rate and long cycle performance according to claim 4, characterized in that: The high temperature sintering is as follows: in an air atmosphere, firstly heating to 400-600°C at a heating rate of 2-6°C / min for 4-6h, then heating to 850-950°C at a heating rate of 2-6°C / min for 10-25h.

9. The method for preparing a sodium-electrode layered metal oxide positive electrode material with high rate and long cycle performance according to claim 8, characterized in that: The high temperature sintering is as follows: in an air atmosphere, firstly heating to 500° C. at a heating rate of 2° C. / min for 5 hours, and then heating to 900° C. at a heating rate of 2° C. / min for 15 hours.

10. The use of the sodium-electrolyte layered metal oxide positive electrode material with high rate and long cycle performance according to any one of claims 1 to 3, characterized in that: Sodium-ion layered metal oxide cathode materials with high rate and long cycle performance are used in sodium-ion batteries.

Citation Information

Cited By

  • Preparation and application of layered oxide positive electrode material of high-rate sodium-ion battery

    CN121237869A